Diversity-oriented synthesis of fused thioglycosyl benzo[e][1, 4]oxathiepin-5-ones and benzo[f][1, 4]thiazepin-5(2H)-ones by a sequence of palladium-catalyzed glycosyl thiol arylation and deprotection–lactonization reactions. Issue 44 (15th September 2015) - AL-Shuaeeb, Riyadh Ahmed Atto; Galvani, Gilles; Bernadat, Guillaume; Brion, Jean-Daniel; Alami, Mouad; Messaoudi, Samir
Abstract : An efficient synthesis of thioglycosylated benzo[ e ][1, 4]-oxathiepin-5-one and benzothiazepinone derivatives has been reported. Abstract : An efficient synthesis of thioglycosylated benzo[ e ][1, 4]oxathiepin-5-one and benzothiazepinone derivatives by a sequence of palladium-catalyzed glycosyl thiol arylation followed by deprotection–lactonization reactions has been reported. This diversity-oriented strategy enabled access to unknown complex cyclic scaffolds with polyhydroxylated appendages of biological interest.